2021
DOI: 10.3389/fphy.2021.666916
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Networks: Forming Cells and Tissues

Abstract: Spatiotemporal changes in viscoelasticity are a key component of the morphogenesis of living systems. Experimental and theoretical findings suggest that cellular- and tissue-scale viscoelasticity can be understood as a collective property emerging from macromolecular and cellular interactions, respectively. Linking the changes in the structural or material properties of cells and tissues, such as material phase transitions, to the microscopic interactions of their constituents, is still a challenge both at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 162 publications
(321 reference statements)
0
18
0
Order By: Relevance
“…Cellular responses to mechanical signals are dependent on the viscoelastic properties of cells, which are largely dependent on the highly dynamic cytoskeleton [ 6 , 7 ]. The viscoelastic properties of the cytoskeleton arise from the properties and dynamic interactions of actin, microtubules, and intermediate fibers [ 8 ]. Intermediate filaments are the most elastic (i.e., the least stiff) and the microtubules are the stiffest component of the cytoskeleton.…”
Section: An Overview Of Cellular Biomechanicsmentioning
confidence: 99%
“…Cellular responses to mechanical signals are dependent on the viscoelastic properties of cells, which are largely dependent on the highly dynamic cytoskeleton [ 6 , 7 ]. The viscoelastic properties of the cytoskeleton arise from the properties and dynamic interactions of actin, microtubules, and intermediate fibers [ 8 ]. Intermediate filaments are the most elastic (i.e., the least stiff) and the microtubules are the stiffest component of the cytoskeleton.…”
Section: An Overview Of Cellular Biomechanicsmentioning
confidence: 99%
“…The material properties of cells are critical components for cell dynamics ( Barriga and Mayor, 2019 ; Corominas-Murtra and Petridou, 2021 ). Increasing evidence suggested that tissue and cells undergo material property change during morphogenesis ( Petridou and Heisenberg, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cell studies suggest that matching the full mechanical profile of tissues allows for healthy cell cultures, reduced activation of inflammatory cells, and enhanced migration of cells through the material. [29,142,[344][345][346] To recapitulate the viscoelastic nature of tissues, surface electrode arrays must be similarly viscoelastic [29,347] or viscoplastic. [30,43,70,348] However, one complexity is that viscoelastic materials are often difficult to process since they have temperature-dependent behaviors.…”
Section: Summary Current Challenges and Future Surface Arraysmentioning
confidence: 99%